2005
DOI: 10.1021/nl0519231
|View full text |Cite
|
Sign up to set email alerts
|

Laser Absorption Scanning Tunneling Microscopy of Carbon Nanotubes

Abstract: We report single molecule laser absorption by carbon nanotubes stamped under ultrahigh vacuum onto Si(100)2x1:H surfaces. Absorption is detected by scanning tunneling microscopy. Images are obtained with and without modulated laser excitation using lock-in amplification and a rear-illumination geometry to reduce thermal effects. Noise appears at topographic edges and is analyzed by a quantitative model in terms of scan speed, mechanical instabilities, and feedback current fluctuations at the edge of the nanotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 20 publications
1
57
0
Order By: Relevance
“…To shine light onto the underlying mechanisms occurring when several external stressors are used simultaneously, STM studies including advanced light‐coupling techniques are desirable. Here, STM techniques such as single‐molecule absorption by STM (SMA‐STM) or novel photocurrent measurement protocols using STM have been developed which have been already applied successfully to other semiconductor systems 34,35,69‐71 . The SMA‐STM technique makes use of a unique light coupling geometry which avoids excessive heating of the tip‐sample junction thus allows precise investigation of the changes in the DOS under illumination.…”
Section: Resultsmentioning
confidence: 99%
“…To shine light onto the underlying mechanisms occurring when several external stressors are used simultaneously, STM studies including advanced light‐coupling techniques are desirable. Here, STM techniques such as single‐molecule absorption by STM (SMA‐STM) or novel photocurrent measurement protocols using STM have been developed which have been already applied successfully to other semiconductor systems 34,35,69‐71 . The SMA‐STM technique makes use of a unique light coupling geometry which avoids excessive heating of the tip‐sample junction thus allows precise investigation of the changes in the DOS under illumination.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that NT1 was pivoted, rather than translated, across the surface, due to attractive interactions with NT2 and NT3 at the junction. The dramatic reduction in noise along the edge of NT1 can likely be attributed to improved alignment between the SWNT axis and the fast‐scan (horizontal) direction of the STM image 18. Moreover, the atomic‐scale cleanliness of the proximal H‐passivated Si(100) surface was not disrupted by the manipulation.…”
Section: Resultsmentioning
confidence: 99%
“…[ 14 ] The group of W. Ho has shown that the absorption of a photon by a molecule involves a tunnel transport mechanism through its excited levels. [ 15 ] LA‐STM has also been extended to the characterization of light absorption by individual inorganic nanostructures such as carbon nanotubes [ 16 ] and quantum dots. [ 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…[14] The group of W. Ho has shown that the absorption of a photon by a molecule involves a tunnel transport mechanism through its excited levels. [15] LA-STM has also been extended to the characterization of light absorption by individual inorganic nanostructures such as carbon nanotubes [16] and quantum dots. [17] In this framework, we have developed a LA-STM setup that aims at mapping the photocurrent resulting from charge transfer at the local scale between a monolayer of a donor polymer: the poly(4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b′] dithiophene-2,6-diyl-alt-3-fluoro-2-[(2-ethylhexyl)carbonyl] thieno [3,4-b]thiophene-4,6-diyl), called PTB7, and an acceptor species: the [6,6]-phenyl-C 71 -butyric acid methyl ester, called PC 71 BM, both successively deposited on the Au(111) surface.…”
mentioning
confidence: 99%